2020
DOI: 10.3390/ijms21165849
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermically Stored Adipose-Derived Mesenchymal Stromal Cell Alginate Bandages Facilitate Use of Paracrine Molecules for Corneal Wound Healing

Abstract: Adipose-derived mesenchymal stromal cells (Ad-MSCs) may alleviate corneal injury through the secretion of therapeutic factors delivered at the injury site. We aimed to investigate the therapeutic factors secreted from hypothermically stored, alginate-encapsulated Ad-MSCs’ bandages in in vitro and in vivo corneal wounds. Ad-MSCs were encapsulated in 1.2% w/v alginate gels to form bandages and stored at 15 °C for 72 h before assessing cell viability and co-culture with corneal scratch wounds. Genes of interest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 93 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Such an approach is being developed for non‐neural transplant transportation where a range of cells have been encapsulated in polymers. [ 32,33 ] This technology could be integrated into a spray device enabling sterile transportation and spraying using a single medical product. Further refinements to develop novel neurosurgical devices seem feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach is being developed for non‐neural transplant transportation where a range of cells have been encapsulated in polymers. [ 32,33 ] This technology could be integrated into a spray device enabling sterile transportation and spraying using a single medical product. Further refinements to develop novel neurosurgical devices seem feasible.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that AD-MSCs can produce paracrine factors, such as VEGF, IGF, and TGF-β, with the potential to improve tissue wound healing 80 , 81 . In the treatment of corneal injury, paracrine factors of AD-MSCs can promote corneal repair by reducing immune infiltration 82 . A study which cocultured AD-MSCs with human corneal epithelial cells found that AD-MSC secretions inhibited TGF-β-induced corneal epithelial–mesenchymal transition 83 .…”
Section: Application Of Mscs In Dry Eye Treatmentmentioning
confidence: 99%
“…Alginate is a natural polysaccharide that can be obtained from seaweed and jellified when cations are added to generate a biocompatible hydrogel [ 23 ]. The advantages of alginate as a simple and cost-effective solution for protecting cell products during storage and transportation have been attributed to its ability to stabilize the membrane of cells in suspension and to protect them from osmotic shock and mechanical stress [ 12 , 24 ]. Alginate encapsulation has potential to impact CGT manufacturing.…”
Section: Introductionmentioning
confidence: 99%